2017
DOI: 10.1177/2325967117707703
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Prevalence and Clinical Characteristics of Humeral Medial Epicondyle Apophysitis and Osteochondritis Dissecans: Ultrasonographic Assessment of 4249 Players

Abstract: Background:Traction apophysitis of medial epicondyle (MEC) lesions and osteochondritis dissecans (OCD) of the capitellum are common elbow injuries in adolescent baseball players. However, the age-specific prevalence of these pathologies and their influence on elbow pain remain unknown.Purpose:To investigate the age-specific prevalence of each MEC lesion and capitellar OCD and to identify the incidence of elbow pain in each condition.Study Design:Descriptive epidemiology study.Methods:Study participants consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐eight articles focused on pain of the elbow and/or shoulder related to overhead sports, published between 1965 and 2017. The studies were conducted in the USA, Japan, Norway, Brazil, Taiwan, and the UK . Sixteen of the articles that reported pain as outcome were cross‐sectional studies, nine articles collected data prospectively, and two studies had a retrospective design …”
Section: Resultsmentioning
confidence: 99%
“…Incidence and prevalence of elbow pain have only been described in baseball players and were 12%‐58% and 17%‐45%, respectively. Seventeen to 63% of youth baseball players reported a history of pain in the elbow. Incidence of shoulder pain was highest among handball‐ (63%) and volleyball players (52%) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Matsuura et al 2 report the incidence of OCD of the capitellum at 1.8% with 23 cases of 1,275 baseball players aged 6 to 11 years over a 1-year period based on screening ultrasound and confirmation with plain radiographs, magnetic resonance imaging, and computed tomography scanning. Using ultrasound as a screening tool in large populations, Matsuura et al 4 found a prevalence of 2.1% of OCD within 1,040 baseball players aged 10 to 12 years; Otoshi et al 5 found a prevalence of 2.2% of OCD within 4,249 baseball players aged 6 to 17 years; and Kida et al 6 found a prevalence of 3.4% of OCD within 2,433 baseball players aged 12 to 18 years. Although not highlighted in this study, by identifying 12 cases of OCD in the initial ultrasound screen of 1,423 baseball players aged 6 to 11 years, the authors found a prevalence of 0.8%.…”
Section: See Related Article On Page 60mentioning
confidence: 99%